Ghosts of Empire in Egypt - Elizabeth Bishop (Université de Provence, 2020)
This article “Ghosts of Empire in Egypte” offer a fresh approach to the Cold War. The full story of Turkey’s ambassador in Egypt and his revenge remained out of the public eye until newspapers offered full details of a plot, clearly aimed at staging: “a military coup, assassinate Gamal Abdul Nasser and other revolution leaders, and re-establishing the monarchy in Egypt.” Great Britain’s prime minister Anthony Eden concluded the maintenance of his country’s Middle Eastern interests demanded the removal of Nasser from power, planning to isolate Nasser inside Egypt, placing a “gradual squeeze on the Egyptian economy in order to ferment popular dissatisfaction with the military regime”.